PENGALAMAN ORANG TUA MENGASUH REMAJA DENGAN AUTISM SPECTRUM DISORDERS (ASD) SAAT PANDEMIK COVID-19 - Lestari, Lilis; Ramadhaniyati, Ramadhaniyati; Triadmodjo, Sigit Imam; Fadila, Yuniar; Tauhidia, Resti Mulya; Utami, Wening Cory (Jurnal Keperawatan dan Kesehatan, 2025)
The COVID-19 pandemic has significantly disrupted educational and healthcare services, including the closure of schools and therapy centers for children and adolescents with Autism Spectrum Disorder (ASD). This situation increased caregiving demands on parents who previously relied on support from teachers and therapists. Adolescents with ASD experience complex developmental impairments that require continuous and specialized care, making the prolonged pandemic particularly challenging for parents in managing caregiving, education, and therapy at home. This study aimed to explore parents’ experiences in caring for adolescents with ASD during the COVID-19 pandemic in Pontianak City, West Kalimantan, Indonesia. A qualitative study with a descriptive phenomenological approach was conducted. Data were collected through focus group discussions with parents of adolescents with ASD aged 9–18 years and analyzed using Colaizzi’s method. The findings identified three main themes: increased caregiving burden, mental health challenges, and parents’ expectations regarding government policies on education and healthcare services for children with ASD. These findings highlight the need for supportive policies and the active involvement of healthcare professionals, particularly nurses, to promote parental well-being and continuity of care during public health crises.